Bibliometric Analysis of Indonesian Journal of Geography from 2015-2022 - Istiana, Purwani; Wicaksono, Pramaditya (Indonesian Journal of Geography, 2025)
This bibliometric analysis aimed to determine the growth trend of document publications, the development of journal citations, the distribution of author countries, the most influential documents, and the dominant research topics in the Indonesian Journal of Geography from 2015 to 2022. The data used were extracted from the Scopus database, comprising a total of 280 documents. A bibliographic data mapping was conducted using the VOSviewer version 1.6.18 and Analyze Search Results tools on the Scopus database. The results showed that the number of documents published in the Indonesian Journal of Geography has been increasing over time. Furthermore, journal impact on scientific development has also increased. The authors of the documents included originate from 29 countries. The most influential document addressed the topic of urban research, while key topics developed from 2015 to 2022 included remote sensing and GIS used as main support and technology for understanding and analyzing various geographical phenomena. This research serves as a reference material for prospective authors and also provides an evaluation of Indonesian Journal of Geography in the future.Received: 2024-09-15 Revised: 2025-01-31 Accepted: 2025-03-19 Published: 2025-04-28